2018
DOI: 10.29252/jcbr.2.4.54
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Kawasaki Disease in Children Admitted to Taleghani Medical Center in Gorgan, Iran

Abstract: Background and objectives: Kawasaki disease is an acute systemic vasculitis of unknown etiology that affects infants and children under 5 years of age. The aim of this study was to investigate the epidemiology of this disease in the Golestan Province, Iran. Methods: This cross-sectional study was performed on all patients (51 individuals) who had been admitted to the Taleghani Hospital in Gorgan (Iran) from September 2005 to October 2012. Characteristics of the patients were extracted from patients' records. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The most common clinical presentation of KD was rash (seen in 62% of patients), oral mucosa and lip involvement (58%), and extremity changes (58%). Our ndings were similar to the ndings of Cheraghali F et al [17] introducing skin rash (68.6%) and changes of the lip and oropharyngeal mucosa (60.8%) as the most common manifestations of KD, but were slightly different from Pilania R.K. et al which showed oral cavity and lips' changes as the most common manifestation (> 95%) of KD, and rash as the second (> 90%). Furthermore, our results showed that neck lymphadenopathy was the least common clinical nding that is compatible with Pilania R.K. et al) [18].…”
Section: Discussionsupporting
confidence: 89%
“…The most common clinical presentation of KD was rash (seen in 62% of patients), oral mucosa and lip involvement (58%), and extremity changes (58%). Our ndings were similar to the ndings of Cheraghali F et al [17] introducing skin rash (68.6%) and changes of the lip and oropharyngeal mucosa (60.8%) as the most common manifestations of KD, but were slightly different from Pilania R.K. et al which showed oral cavity and lips' changes as the most common manifestation (> 95%) of KD, and rash as the second (> 90%). Furthermore, our results showed that neck lymphadenopathy was the least common clinical nding that is compatible with Pilania R.K. et al) [18].…”
Section: Discussionsupporting
confidence: 89%
“…The most common clinical presentation of KD was rash (seen in 62% of patients), oral mucosa and lip involvement (58%), and extremity changes (58%). Our ndings were similar to the ndings of Cheraghali F et al [17] introducing skin rash (68.6%) and changes of the lip and oropharyngeal mucosa (60.8%) as the most common manifestations of KD, but were slightly different from Pilania R.K. et al which showed oral cavity and lips' changes as the most common manifestation (> 95%) of KD, and rash as the second (> 90%). Furthermore, our results showed that neck lymphadenopathy was the least common clinical nding which is compatible with Pilania R.K. et al) [18].…”
Section: Discussionsupporting
confidence: 89%
“…A total of 40% of our patients experienced conjunctivitis. Rates mentioned in the literature are higher (Cheraghali et al [ 2 ] 51%; Mahmoudzadeh et al [ 18 ] 83%). We believe providing education to patients regarding the prevention of conjunctivitis was a beneficial factor in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the leading theory is that an unknown infectious agent activates the immune system in a genetically vulnerable child. Kawasaki disease is more prevalent among males and most studies have mentioned a gradual increase in the number of cases from March to June [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation